The Quranic Cosmological Argument in Islamic Intellectual History: Fakhr Al-Din Al-Razi on the Creation of Heavens In Verse 1 of Surah Al-An’am - Mohd Saiful Aqil Naim Saful Amin; Wan Adli Wan Ramli; Syed Mohammad Hilmi Syed Abdul Rahman (Journal Al-Muqaddimah, 2025)
This study examines the Quranic cosmological argument as articulated by the classical Ash‘arite theologian and exegete, Fakhr al-Dīn al-Rāzī (d. 606 AH), in his commentary on the first verse of Sūrah al-An‘ām. In an intellectual climate dominated by secular and materialistic worldviews, which posit a purposeless, self-contained universe, this research posits that al-Rāzī’s exegesis offers a sophisticated philosophical rebuttal. The paper delineates how al-Rāzī extrapolates a comprehensive metaphysical architecture from the verse, employing linguistic analysis, geometric analogy, and a rigorous tenfold argument from contingency (dalīl al-imkān) to demonstrate that every aspect of the cosmos, from its macroscopic structure to its fundamental motions, is contingent and thus necessitates a transcendent, voluntary Creator (al-Fā‘il al-Mukhtār). The core of al-Rāzī’s method is shown to be grounded in the Ash‘arite doctrine of occasionalism, which posits God as the sole and direct cause of all events. The study concludes by arguing that this classical framework is not a historical artifact but a vital intellectual tool for deconstructing the metaphysical assumptions of modern atheism, particularly Darwinian and New Atheist claims, and for providing a coherent, theocentric paradigm that reconciles divine sovereignty with a rational understanding of the natural world.